Use of silver nanoparticles increased inhibition of cell-associated HIV-1 infection by neutralizing antibodies developed against HIV-1 envelope proteins - Lara Villegas, Humberto Herman; Ixtepan Turrent, Liliana del Carmen; Garza Treviño, Elsa Nancy; Singh, Dinesh K. (2011)
Background: HIV/AIDS pandemic is a worldwide public health issue. There is a need for new approaches to develop new antiviral compounds or other therapeutic strategies to limit viral transmission. The envelope glycoproteins gp120 and gp41 of HIV are the main targets for both silver nanoparticles (AgNPs) and neutralizing antibodies. There is an urgency to optimize the efficiency of the neutralizing antibodies (NABs). In this study, we demonstrated that there is an additive effect between the four NABs and AgNPs when combined against cellassociated HIV-1 infection in vitro Results: Four NABs (Monoclonal antibody to HIV-1 gp41 126-7, HIV-1 gp120 Antiserum PB1 Sub 2, HIV-1 gp120 Antiserum PB1, HIV-1 gp120 Monoclonal Antibody F425 B4e8) with or without AgNPs of 30-50 nm in size were tested against cell free and cell-associated HIVIIIB virus. All NABs inhibited HIV-1 cell free infection at a dose response manner, but with AgNPs an antiviral additive effect was not achieved Although there was no inhibition of infection with cellassociated virus by the NABs itself, AgNPs alone were able to inhibit cell associated virus infection and more importantly, when mixed together with NABs they inhibited the HIV-1 cell associated infection in an additive manner. Discussion: The most attractive strategies to deal with the HIV problem are the development of a prophylactic vaccine and the development of effective topical vaginal microbicide. For two decades a potent vaccine that inhibits transmission of infection of HIV has been searched. There are vaccines that elicit NABs but none of them has the efficacy to stop transmission of HIV-1 infection. We propose that with the addition of AgNPs, NABs will have an additive effect and become more potent to inhibit cell-associated HIV-1 transmission/infection. Conclusions: The addition of AgNPs to NABs has significantly increased the neutralizing potency of NABs in prevention of cell-associated HIV-1 transmission/infection. Further exploration is required to standardize potentiation of NABs by AgNPs. It is also required to evaluate in vivo toxicity of AgNPs before AgNPs could be incorporated in any antiviral vaginal creams.